2019
DOI: 10.1292/jvms.19-0256
|View full text |Cite
|
Sign up to set email alerts
|

Effect of combined vaccination for <i>Pasteurella multocida</i>, <i>Mannheimia haemolytica</i>, and <i>Histophilus somni</i> to prevent respiratory diseases in young Japanese Black calves in the field

Abstract: To evaluate the preventive effects of combined vaccination for Pasteurella multocida, Mannheimia haemolytica and Histophilus somni on respiratory diseases in Japanese Black calves, 295 calves at one farm were alternately assigned to two groups; 147 calves received the vaccine at 4 and 8 weeks of age (vaccination group), and the other 148 calves did not receive vaccine (control group). The incidences of respiratory diseases were 25.9 and 70.9% in the vaccination and control groups, respectively, and the odds ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
(18 reference statements)
1
5
0
Order By: Relevance
“…These four factors were previously found to be strongly associated with the health status of calves (6,8,17,18). It has already been reported that a significant reduction in the incidence of respiratory disease as well as higher antibody titres in responses detected using the same antigen were observed in calves immunised with the same vaccine as the one used in this study (16). Therefore, early immunisation probably mitigates BRD in young calves, and the health status of calves at immunisation is very important for preventing BRD.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…These four factors were previously found to be strongly associated with the health status of calves (6,8,17,18). It has already been reported that a significant reduction in the incidence of respiratory disease as well as higher antibody titres in responses detected using the same antigen were observed in calves immunised with the same vaccine as the one used in this study (16). Therefore, early immunisation probably mitigates BRD in young calves, and the health status of calves at immunisation is very important for preventing BRD.…”
Section: Discussionsupporting
confidence: 69%
“…Blood samples were collected into plain vacutainer tubes and centrifuged at 3,500 rpm for 8 min, and the serum was isolated. Serum was maintained at −30℃ until analysis and serum antibodies against H. somni , P. multocida and M. haemolytica were detected using an ELISA as previously described ( 16 ). When the antibody titres for P. multocida and M. haemolytica were detected with less than a 100-fold dilution, they were calculated as a 50-fold dilution.…”
Section: Methodsmentioning
confidence: 99%
“…Blood samples were collected into plain vacutainer tubes and centrifuged at 3,500 rpm for eight min, and then blood serum was isolated. Serum was kept at −30°C until analysis and serum antibodies against H. somni, P. multocida, and M. haemolytica were detected using ELISA as described in a previous study (15). For P. multocida and M. haemolytica, when the antibody titre was detected with less than 100-fold dilution, it was calculated as a 50-fold dilution.…”
Section: Methodsmentioning
confidence: 99%
“…Challenge studies, whilst important for determining the potential for a vaccine to be effective, have the disadvantages of an atypical environment and unnatural timings of pathogen exposure. Certain field trials have reported significantly lowered morbidity and mortality in vaccinated calves compared to non-vaccinated calves with multivalent vaccines against [ 133 , 134 , 135 ]. However, there is a lack of field trials investigating the prevention of BRDC for the many vaccines that have been developed.…”
Section: Vaccination Challengesmentioning
confidence: 99%